2018
DOI: 10.1007/s11121-018-0897-2
|View full text |Cite
|
Sign up to set email alerts
|

What Influences Parental Engagement in Early Intervention? Parent, Program and Community Predictors of Enrolment, Retention and Involvement

Abstract: Poor participant engagement undermines individual and public health benefits of early intervention programs. This study assessed the extent to which three types of engagement (participant enrolment, retention and involvement) were influenced by individual, program and contextual factors. Data were from a cluster randomised controlled trial (N = 1447) of a community-based parenting program, delivered at two levels of intensity (group sessions with and without individualised home coaching) conducted in Victoria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 31 publications
5
43
0
Order By: Relevance
“…One of these parents found the information about the risk of suicide in adolescents confronting and indicated that she was worried her adolescent was at higher risk due to having a chronic health condition. The parent said it “ made her think about some things and more aware that her son might be at greater risk because he has diabetes and has factors associated with that that he needs to worry about .” Another parent reported finding the ‘Good health habits’ module, which covers four health behaviours, including substance use, difficult to complete as “ she found out he had been doing drugs .” These comments support the findings of online intervention research (Hackworth et al, 2018) that indicates having a coach with whom to process the information may be helpful to parents in such situations, where the child is already experiencing various challenges.…”
Section: Resultssupporting
confidence: 68%
“…One of these parents found the information about the risk of suicide in adolescents confronting and indicated that she was worried her adolescent was at higher risk due to having a chronic health condition. The parent said it “ made her think about some things and more aware that her son might be at greater risk because he has diabetes and has factors associated with that that he needs to worry about .” Another parent reported finding the ‘Good health habits’ module, which covers four health behaviours, including substance use, difficult to complete as “ she found out he had been doing drugs .” These comments support the findings of online intervention research (Hackworth et al, 2018) that indicates having a coach with whom to process the information may be helpful to parents in such situations, where the child is already experiencing various challenges.…”
Section: Resultssupporting
confidence: 68%
“…A key limitation of community-based parenting interventions is that they are usually offered as one-size-fits-all packages, which stands in contrast to evidence that parents differ in the techniques that are most applicable to them, [1][2][3][4] and therefore require tailored approaches. [5] Tailoring may take into account parents' needs or their day-today parenting context.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11]. In contrast, tailoring related to parenting context has been minimal, despite the potential for this approach to increase parent engagement and intervention efficacy, in light of low rates of homework completion in parenting interventions, [3] and recognized limitations in the human ability to generalize skills outside of specific learning contexts. [12] To enable a more systematic way of tailoring interventions to specific parenting situations, and thus facilitate parents to immediately implement intervention concepts in their daily lives, the field requires an accurate map of the wide range of day-to-day parenting situations that parents may need support with.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have examined the relationship between parental involvement and parental demographics [3], [6]- [8]. Factors related to demographics are parent and child age and gender, family structure and size, parent education, employment status, household income, government benefits, language spoken at home [6]. Research has been conducted to evaluate the relationship between demographic, parental, and cognitive, linguistic, and motor skills development in children with learning disabilities [7].…”
Section: Introductionmentioning
confidence: 99%